THE EFFECT OF JENGKOL SEED (Archidendron pauciflorum) EXTRACT TO PLASMA MDA LEVEL DUE TO DEEP SECOND DEGREE BURN WOUND IN SPRAGUE DAWLEY RATS - Kurniati, Steffi; Batubara, Lusiana; Wikanta, Edmond Rukmana; Johan, Andrew (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: During inflammatory phase of the burn healing process, the number of plasma MDA levels tend to increase, which may cause damage towards cells and thus delay the resolution of burn wounds. Some research has been done in order to find alternative treatment for burn wound, including the application of antioxidant. Jengkol contains many antioxidant compounds which are expected to reduce plasma MDA levels, so it can accelerate the healing of burn wound. Aim: To prove that administration of jengkol extract can reduce plasma MDA level in Sprague dawley rats which were been given burn wound. Method: This experiment was using pre and post-test control group design, with 20 Sprague dawley rats as samples. All of the samples were given deep second degree burn wound which were then divided equally into 2 groups, treatment group (given jengkol extract 500 mg/KgBW) and control group (not given anything). Plasma MDA levels were then analyzed by using TBARS method. Data was analyzed using paired T-test, Wilcoxon, Mann-Whitney, and independence T-test. Result: There is no significant difference between the mean of plasma MDA levels in pre and post-test of either control group (p=0.771) or in the treatment group (p=1.00). Using Mann-Whitney test, there isn’t any significant difference in the pre-test between control and treatment group (p=0.677) or in the post-test between control and treatment group (p=0.916) by using independence T-test. Conclusion: Jengkol extract cannot reduce plasma MDA levels of Sprague dawley rats which were given burn wound.